An Intraoperative Serum Parathormone Level Study in Patients with Chronic Renal Failure That Underwent Subtotal Parathyroidectomy What Extent of Decrease Is Sufficient at Which Moment - Tarim, Ismail Alper; Kesicioglu, Tugrul; Karabulut, Kagan; Derebey, Murat; Mizan, Salih Rasit; Akgun, Can; Polat, Cafer (Edizioni Luigi Pozzi, 2021)
AIM: The aim of this study is to determine when to perform intraoperative parathormone (ioPTH) measurement and what extent of decrease in intraoperative serum PTH concentrations indicate success in the operations performed on patients with SHPT associated with chronic renal failure. MATERIAL AND METHODS: 50 consecutive patients who underwent subtotal parathyroidectomy between January 2012 and January 2019 were retrospectively included in this study. Patients were grouped according to persistent hyper parathyroidism (Group1, n:6) and curative surgery (Group 2, n:44). Preoperative serum PTH, calcium, phosphorus and ALP concentrations, intraoperative serum PTH concentrations; and serum PTH, calcium, phosphorus and ALP concentrations of 24th hour after surgery were included to the study. Intraoperatively, 20 minutes after parathyroid gland removal, blood was drawn for PTH assay. The changes in PTH levels between preoperative and intraoperative serum samples were calculated in percentage (ioPTH%) and postoperative 6th month serum PTH and ALP concentrations were included in the study. RESULTS: No significant differences were found by gender, BMI, elapsed period of dialysis treatment and preoperative laboratory values between Group 1 and Group 2. The meanage of Group 1 was 35 years which is lower than Group 2. With the second group, the mean decrease in PTH levels between intraoperative and preoperative serum samples (ioPTH%) was about 90%, which was higher than Group 1. CONCLUSIONS: In conclusion, we believe that, to encounter fewer persistent SHPT cases, it is essential that surgeons monitor ioPTH concentration 20 minutes after gland removal and confirm a decrease of 90% or more in ioPTH concentration. And we should not forget that young patients may tend to develop persistent SHPT.
Keywords: Chronic Renal Failure; Intraoperative Parathormone; Secondary Hyperparathyroidism; Parathyroidectomy; Subtotal Parathyroidectomy